Anthropology in the land of equivocations: Peruvian subtleties among the Yánesha of the Peruvian Amazon - Narro, André (2018)
Pandoras’s box for many, indigenous peoples’ political field continues to arouse surprises, followed by hasty conclusions by the media and even in academic circles. Trying to give content to the structures and form to the experiences of the Yanesha leaders, the itinerary of this chronicle begins with the subtleties of the practices that inform this field, then, to follow its development through diverse paradoxes.All this, through the account of the three days of October of 2016, during which the Extraordinary Congress of the Federation of Yanesha Native Communities took place.